GROWTH AND PRODUCTION OF Pennisetum purpureum cv. Mott FERTILIZED WITH FERMENTED LIQUID FERTILIZER DRGONS FRUIT WASTEON SOIL ADDED LIME - M. D. I., Zaki; Witariadi, N. M.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
This study aims to determine the growth and yield of Pennisetum purpureum cv. Mott fertilized with fermented dragon fruit waste liquid fertilizer on soil added with lime, has been carried out in a greenhouse, Sesetan Research Station, Faculty of Animal Science, Udayana University on Sesetan Street. The study lasted for 12 weeks from preparation to data collection, using a Completely Randomized Design (CRD) with 6 treatments and 5 replications so that there were 30 experimental units. The treatments were D0 : 0 l ha-1, D1 : 2,500 l ha-1, D2 : 5,000 l ha-1, D3 : 7,500 l ha-1, D4 : 10,000 l ha-1, and D5 : 12,500 l ha-1. The variables observed were growth variables; plant height, number of leaves, number of tillers, clump circumference, yield variable; leaf dry weight, stem dry weight, root dry weight, total dry weight of forage and variable growth characteristics; ratio of dry weight of leaves to dry weight of stems, ratio of total dry weight of forage to dry weight of roots, and leaf area per pot. The results showed that fermented dragon fruit waste liquid fertilizer on soil added with lime did not increase growth and yields except for the circumference of the grass clump Pennisetum purpureum cv. Mott. It can be concluded that the application of fermented dragon fruit waste liquid fertilizer to the soil added with lime has not resulted in an increase in growth and yield except for the circumference of the grass clump Pennisetum purpureum cv. Mott..